Perioperative care of an adolescent with postural orthostatic tachycardia syndrome - Kernan Scott (Saudi Journal of Anaesthesia, 2010)
Postural orthostatic tachycardia syndrome (POTS) is a disorder characterized by postural tachycardia in combination with orthostatic symptoms without associated hypotension. Symptoms include light-headedness, palpitations, fatigue, confusion, and anxiety, which are brought on by assuming the upright position and usually relieved by sitting or lying down. Given the associated autonomic dysfunction that occurs with POTS, various perioperative concerns must be considered when providing anesthetic care for such patients. We present an adolescent with POTS who required anesthetic care during posterior spinal fusion for the treatment of scoliosis. The potential perioperative implications of this syndrome are discussed.